PERAN DAN KEDUDUKAN EMPAT PILAR DALAM PENEGAKAN HUKUM HAKIM JAKSA POLISI SERTA ADVOCAT DIHUBUNGKAN DENGAN PENEGAKAN HUKUM PADA KASUS KORUPSI - Ali Imron (Universitas Pamulang, 2016)
This research explains the role of the four pillars in law enforcement judges, prosecutors, police and advocates. primarily address corruption need to be instilled sense of justice and implanted